The provision of enteral nutritional support during definitive chemoradiotherapy in head and neck cancer patients - Bishop, Sarah (J Med Radiat Sci, 2015)
Combination chemoradiation is the gold standard of management for locally advanced squamous cell carcinomas of the head and neck. One of the most significant advantages of this approach to treatment is organ preservation which may not be possible with radical surgery. Unfortunately, few treatments are without side‐effects and the toxicity associated with combined modality treatment causes meaningful morbidity. Patients with head and neck cancer (HNC) may have difficulties meeting their nutritional requirements as a consequence of tumour location or size or because of the acute toxicity associated with treatment. In particular, severe mucositis, xerostomia, dysgeusia and nausea and vomiting limit intake. In addition to this, dysphagia is often present at diagnosis, with many patients experiencing silent aspiration. As such, many patients will require enteral nutrition in order to complete chemoradiotherapy (CRT). Feeding occurs via catheters placed transnasally (nasogastric tubes) or directly into the stomach through the anterior abdominal wall (percutaneous gastrostomy tubes). In the absence of clear evidence concerning the superiority of one method over another, the choice of feeding tube tends to be dependent on clinician and patient preference. This review examines key issues associated with the provision of enteral nutritional support during definitive CRT in HNC patients, including feeding methods, patient outcomes and timing of tube insertion and use.